DIETARY PRACTICAL INGREDIENTS WITH EMPHASIS ON PROTEIN SOURCES FOR PENAEID SHRIMP - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Studies on the utilization of dietary practical ingredients, in particular protein sources, by penaeid shrimp juveniles were reviewed in this paper.  It has been proved by a number of researchers in shrimp nutrition that diets containing a mixture of two or more protein sources are better utilized by shrimp than those containing single protein sources.  In general, evaluation of the nutritive value of a feed ingredient for growth is based on both the quantity and the quality of the protein in the ingredient.  The amino acid composition and the relative proportions of other dietary nutrients are mostly relevant to the efficiency of protein assimilation by penaeids.  Based on the essential amino acid index (EAAI) used to screen some potential protein sources for penaeid shrimp, there were found that fish meal, shrimp meal, squid meal and soybean meal were good dietary potential protein sources with EAAIs between 0.87-0.98.